2001
DOI: 10.1080/09593332208618192
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Ammonia as Struvite from Anaerobic Digester Effluents

Abstract: The effects of environmental conditions on ammonia removal as struvite (Magnesium ammonium phosphate, MAP) were studied in a laboratory scale batch reactor. MAP precipitation was carried out by adding phosphoric acid and magnesium source either as MgCl, or MgO. The effect of temperature, pH, MgN:P ratios were studied. Temperature did not significantly affect ammonia removal between 25-40 degrees C and over 90% removal was obtained. The effect of pH, however,was significant and highest removal was reached at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 0 publications
4
41
2
2
Order By: Relevance
“…The use of MgCl 2 as an alternative Mg source in struvite precipitation studies [18,41] showed that more nitrogen could be recovered as ammonia. The negative effect is that struvite formation is optimal at a pH between 8.9 and 9.2, and when using MgCl2 the pH must be adjusted by adding other chemicals, such as NaOH.…”
Section: Phosphate Uptakementioning
confidence: 99%
“…The use of MgCl 2 as an alternative Mg source in struvite precipitation studies [18,41] showed that more nitrogen could be recovered as ammonia. The negative effect is that struvite formation is optimal at a pH between 8.9 and 9.2, and when using MgCl2 the pH must be adjusted by adding other chemicals, such as NaOH.…”
Section: Phosphate Uptakementioning
confidence: 99%
“…As one of the attractive processes for the removal of phosphate and ammonium from wastewater, the MAP process has been received attention [1][2][3][4][5]:…”
Section: Introductionmentioning
confidence: 99%
“…The formation of these products removes some of the Mg 2+ and PO 4 3− available for struvite crystallization, therefore, an overdose of reagents is necessary. In further researches, the benefit of overdosing magnesium and phosphorus was verified [18,19,32]. Clearly, the optimal dosages reported in the literature are related to many factors, such as the characteristics of treated wastewaters, the exploited reactants, and the applied process conditions.…”
Section: Struvite Productionmentioning
confidence: 99%
“…However, the development of effective and economic methods for the abatement of the high nitrogen loads of wastewaters still represents a big issue [14,15]. In this regard, the precipitation of ammonium as struvite is a promising approach, due to its high process efficiency and the ease of management [16][17][18][19][20][21][22][23][24][25][26][27]. Struvite crystals are composed of Mg +2 , NH 4 + , and PO 4 3− in equimolar amounts (MgNH 4 PO 4 ·6H 2 O) [16,17].…”
Section: Introductionmentioning
confidence: 99%